INFLUENCE OF THE INTERNAL ACCOUNTING AUDIT IN THE FINANCES OF THE TEXTILE COMPANIES OF THE GAMARRA COMMERCIAL EMPORY IN PERU - Chenet Zuta, Manuel Enrique (2019)
The objective of the investigation was todetermine the influence of the internal accountingaudit on the finances of the textile companies ofthe commercial empire of Gamarra located in thedistrict of La Victoria in the department of Lima,capital of Peru. The study was of the basic type,descriptive level and causal correlational design.To measure and then correlate both variables, asurvey questionnaire was applied to a sample of132 accountants, administrators and businessmenwho are in charge of the management of 12 textilecompanies that offer their products in the Gamarracommercial emporium. The review of the scientificliterature included the analysis of the InternationalAuditing Standards (NIAS), the Generally AcceptedAuditing Standards (NAGAS) and the InternationalStandards for the Exercise of Internal Audit (IIA).The correlation coefficient r was 0.94, while thecoefficient of determination R2 was 0.88. Accordingto these figures, the internal accounting auditexplains 88% of the finances in these companies.It was determined that the internal audit generatesadded value to the company, minimizing financialrisk and improving the position towards itscompetitors.